A humument : a treated Victorian novel - Phillips, Tom (London : Thames & Hudson, 2012)
In the mid-1960s, Tom Phillips took a forgotten nineteenth-century novel, W. H. Mallock's A Human Document, and began cutting and pasting the extant text to create something new. This new fifth edition of Tom Phillipss perennially popular book follows its predecessors by incorporating revisions and re-workings over half the pages in the 1980 edition are replaced by new versions and celebrates an artistic enterprise that is over 45 years old and still actively a work in progress.
boek